POLA PENGEMBANGAN INTEGRATIF STUDI AL-QUR’AN DI PERGURUAN TINGGI ISLAM: ANALISIS ATAS GAGASAN INTEGRATIF DI UIN SUNAN KALIJAGA YOGYAKARTA - Ghozali, Mahbub; Murtaza MZ, Ahmad (UIN Sumatera Utara Medan, 2023)
The progress of contemporary knowledge has implications for the formulation of Islamic studies in general, including the examination of the Qur'an. Scholars at UIN Sunan Kalijaga Yogyakarta are redefining the approach to studying the Qur'an in a more modern direction to foster synergy and dialogue with established practices. The objective of this research is to uncover patterns and mechanisms for advancing Qur'anic studies at UIN Sunan Kalijaga by effectively integrating scientific methods and the teachings of the Qur'an. In order to accomplish this, the research employs a qualitative methodology and utilizes a systematic literature review as an analytical technique. The study reveals a developmental pattern in Qur'anic studies at UIN Sunan Kalijaga that commenced with a shift in perspective from a traditional emphasis on religious texts (ulūm ad-din) to critical investigations (dirāsāt islamīyah) based on empirical observations. Consequently, a fresh and contemporary model of Qur'anic studies has emerged. However, the application of these novel concepts encounters challenges, particularly in student research, where passivity impedes active involvement in the advancement of Qur'anic studies.